Comprehensive Approach to Acute Pulmonary Embolism in a Patient with History of Cervical Cancer: Clinical Challenges and Therapeutic Strategies - Arya Wiradarma; Putu Andrika (MEDICINUS, 2026)
Pulmonary embolism (PE) is a life-threatening medical emergency that requires prompt diagnosis and treatment, particularly in patients with significant risk factors such as a history of cancer. This case report discusses a 45-year-old female with a history of stage IIIA cervical cancer who presented with acute onset dyspnea and hemodynamic instability. The patient’s prior cancer treatments, including chemotherapy and radiotherapy, increased the patient’s risk for venous thromboembolism (VTE), leading to acute pulmonary embolism. The diagnosis was confirmed by computed tomography pulmonary angiography (CTPA), which revealed a substantial thrombus obstructing the left pulmonary artery. Laboratoryfindings showed markedly elevated D-dimer levels. Further assessment with echocardiography (echo) revealed right ventricular (RV) dysfunction, a critical marker of hemodynamic stress caused by the embolism. The echo findings included RV hypokinesis, an increased right ventricle/left ventricle (RV/LV) ratio, and possible tricuspid regurgitation, all of which indicated severe right heart strain. These findings serve as key prognostic indicators in acute PE, correlating with a higher risk of mortality and guiding therapeutic decision-making. The comprehensive management approach for this patient highlights the importance of rapid diagnosis, risk stratification, and aggressive therapeutic interventions in highriskPE. Echocardiographic findings played a crucial role in determining the disease severity and informing the need for potential reperfusion therapies, such as thrombolysis or surgical embolectomy. This case emphasizes the importance of integrating clinical, imaging, and laboratory data to optimize patient outcomes. Echocardiography plays a pivotal role inmonitoring right ventricular function and adjusting treatment strategies in PE, particularly among oncology patients who are at increased risk.